Design Optimization Of PV And WTE Integration In Electricity Supply System For Mandalay Urban Area - Oo, Hay Man; Swe, Wunna (AI Society & STMIK Indonesia, 2024)
Hybrid energy systems, which combine two or more energy systems, arebecoming increasingly popular due to the rise in petroleum productprices, growing CO2 emission awareness, and advancements in renewableenergy technologies. These systems are being adopted to meet the energyand electricity demands of decentralized networks. In Myanmar, someareas still face significant challenges in accessing grid-based electricitysupply. In such cases, the hybrid renewable microgrid systems offer abetter alternative by reducing dependency on diesel fuel and meetingenergy demands in an environmentally friendly manner. To enhance thereliability of these hybrid systems, renewable sources can be integratedwith diesel generators and utility grid. This integration allows hybridsystems to compensate for the intermittent nature of renewable energysources and achieve higher overall energy efficiency. One of the mainadvantages of hybrid systems is their potential for energy autonomy, asthey are not reliant on a single energy source. This paper introduces anovel approach for designing a grid connected hybrid system thatincorporates photovoltaic, and biomass especially the municipal solidwaste. The Hybrid optimization model for electrical renewable (HOMER)is a powerful optimization model that simplifies the evaluation of off-gridand grid-connected power system designs for various applications. In thispaper, the grid connected hybrid renewable energy system is designedand analyze for Mandalay region.